Assessment of learning - Harlen, Wynne (SAGE, 2007)
'Assessment of Learning' takes a critical look at how students' achievements are assessed for a range of purposes, from reporting progress to selection and qualification. It considers the relationship between what is taught, and how, and what and how learning outcomes are assessed.
Keywords: Educational tests and measurements : Evaluation; Educational tests and measurements : Evaluation